2007
DOI: 10.1007/s11195-007-9064-6
|View full text |Cite
|
Sign up to set email alerts
|

Disability, Gender and Intimate Partner Violence: Relationships from the Behavioral Risk Factor Surveillance System

Abstract: Research on women with disabilities has found that the most common perpetrators of violence were current or former intimate partners (Young et al. Arch. Phys. Med. Rehabil. 78, S34-S38, 1997; Riddington, Beating the ''odds'': Violence and Women with Disabilities (Position Paper 2). 1989). This article examines intimate partner sexual and physical abuse experienced by women with disabilities compared to women without disabilities and men with and without disabilities through chi square analysis and regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 25 publications
4
100
0
4
Order By: Relevance
“…También parece confirmarse que dicho patrón de riesgo es mayor al que puede presentarse en poblaciones sin discapacidad y que las mujeres son las más afectadas (Nosek et al, 2001;Smith, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…También parece confirmarse que dicho patrón de riesgo es mayor al que puede presentarse en poblaciones sin discapacidad y que las mujeres son las más afectadas (Nosek et al, 2001;Smith, 2008).…”
Section: Discussionunclassified
“…La investigación realizada por Smith (2008) comparó situaciones de abuso en poblaciones estadounidenses de hombres y mujeres con discapacidad y sin ella. Los resultados indicaron que hombres y mujeres con discapacidad viven diversas formas de violencia -incluyendo amenazas, intentos, violencia física real, así como relaciones sexuales no deseadas-, pero que son las mujeres con discapacidad quienes viven estas situaciones con mayor frecuencia.…”
Section: Introductionunclassified
“…Disability theory points to the isolation, lack of power, and unequal access to resources that persons with disabilities experience (Smith, 2007). Disability theory moves beyond traditional theories of domestic abuse and violence that do not adequately account for the experiences of persons with disabilities and have not considered the effects of marginalization and oppression of those who have disabilities (Mays, 2006;Smith & Anderson, 2004).…”
Section: Disability Theorymentioning
confidence: 99%
“…Disability theory moves beyond traditional theories of domestic abuse and violence that do not adequately account for the experiences of persons with disabilities and have not considered the effects of marginalization and oppression of those who have disabilities (Mays, 2006;Smith & Anderson, 2004). Many studies have found that women with disabilities are at a higher risk for IPV than women without disabilities (Brownridge, 2006;Brownridge, Ristock, & Hiebert-Murphy, 2008;Chenoweth, 1997;Collins et al, 1999;Hague, Thiara, & Magowan, 2007;Luthra & Gidycz, 2006;McFarlane et al, 2001;Nosek et al, 1995;Smith, 2007;Sobsey & Doe, 1991;Young, Nosek, Howland, Chanpong, & Rintala, 1997).…”
Section: Disability Theorymentioning
confidence: 99%
“…Adding to this, Smith's (2008) analysis of the frequency of interpersonal violence for women with disabilities strongly recommended that interventions need to be developed that will support women who are at risk of interpersonal violence and in particular, strengthen assessment procedures to identify women who are experiencing interpersonal violence. Lund In sum, there are a number of social dynamics which create real barriers for women with disabilities and in tum, make women with disabilities vulnerable to interpersonal violence.…”
Section: Lack Of Knowledge Despite Numerous Studies Demonstrating Thmentioning
confidence: 99%